2023
DOI: 10.1097/cm9.0000000000002361
|View full text |Cite
|
Sign up to set email alerts
|

Association between low ambient temperature during pregnancy and adverse birth outcomes: a systematic review and meta-analysis

Abstract: Background: Extreme temperature events, including extreme cold, are becoming more frequent worldwide, which might be harmful to pregnant women and cause adverse birth outcomes. We aimed to investigate the association between exposure to low ambient temperature in pregnant women and adverse birth outcomes, such as preterm birth, low birth weight, and stillbirth, and to summarize the evidence herein. Methods: Relevant studies were searched in PubMed, Cochrane, and Embase electronic databases until November 2021.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Our findings on the association of low temperature and increased risk of PTBs are consistent with a previous review that included 34 studies. 8 For example, a study conducted in Guangzhou, China, involving 838 146 singleton vaginal births, revealed that exposures to extreme cold (the 1st percentile, 7.6°C) during the last 4 weeks of pregnancy were associated with a 17.9% (95% CI 10.2-26.2) increased risk of PTBs. 45 A meta-analysis of nine studies confirmed a 14% (95% CI 6-23) increased risk of PTBs associated with low (<1st percentile) temperature, 8 which is comparable to our findings.…”
Section: Interpretationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our findings on the association of low temperature and increased risk of PTBs are consistent with a previous review that included 34 studies. 8 For example, a study conducted in Guangzhou, China, involving 838 146 singleton vaginal births, revealed that exposures to extreme cold (the 1st percentile, 7.6°C) during the last 4 weeks of pregnancy were associated with a 17.9% (95% CI 10.2-26.2) increased risk of PTBs. 45 A meta-analysis of nine studies confirmed a 14% (95% CI 6-23) increased risk of PTBs associated with low (<1st percentile) temperature, 8 which is comparable to our findings.…”
Section: Interpretationsmentioning
confidence: 99%
“…8 For example, a study conducted in Guangzhou, China, involving 838 146 singleton vaginal births, revealed that exposures to extreme cold (the 1st percentile, 7.6°C) during the last 4 weeks of pregnancy were associated with a 17.9% (95% CI 10.2-26.2) increased risk of PTBs. 45 A meta-analysis of nine studies confirmed a 14% (95% CI 6-23) increased risk of PTBs associated with low (<1st percentile) temperature, 8 which is comparable to our findings. Even though people dress warmly in cold weather, exposure to low temperatures, for example on the face, can lead to vasoconstriction, 46 potentially affecting PTB by reducing uteroplacental blood flow.…”
Section: Interpretationsmentioning
confidence: 99%
See 3 more Smart Citations